Atomically Thin Semiconductor TiPtGe and Heterostructure of β‑Antimonene/TiPtGe: A First-Principles Study - Liu, Kai; Liu, Zhao; Wang, Jing; Song, Juntao; Liu, Ying (Journal of physical chemistry. C, 2023)
Half-Heusler intermetallic compounds have been an important subject of interest in the field of semiconductors for years, but have been studied more for their bulk structure and rarely for their two-dimensional structure. Here, a novel two-dimensional semiconductor material with the chemical formula TiPtGe and an indirect bandgap of 1.27 eV has been developed on the basis of first-principles calculations. Significantly, it could be transformed from an indirect to a direct bandgap semiconductor under small biaxial in-plane strain. Given the similar lattice parameters and symmetry with the single-element two-dimensional material antimonene, we have attempted to form a vertical heterostructure of the two. The calculated results show that the heterostructure can be transformed from an indirect to a direct bandgap by increasing the number of TiPtGe layers. Further calculated results of the optical properties show that increasing the number of TiPtGe layers in the heterostructure could significantly improve the absorption efficiency in the visible region. This provides a new possibility for the application of antimonene in optoelectronic devices.